Navigating nutritional norms: a deep dive into the social cognitive factors and communication patterns shaping food behaviors among cis-gendered collegiate male runners - Randall, Benjamin Spencer, author; Abrams, Katie, advisor; Martey, Rosa Mikeal, committee member; Graham, Dan, committee member (Colorado State University. Libraries, 2025)
Throughout history, food has shaped human relationships, impacting not only physical health but also emotional well-being and social behaviors. This thesis explored the interplay between personal cognition, social factors, and environmental cues influencing food-related behaviors among cis-gendered male collegiate distance runners. Focusing on athletes competing in highly demanding endurance sports, this study examined how interpersonal communication within teams shapes nutritional choices and behaviors. Using a qualitative approach, interviews were conducted with current and former collegiate athletes, and data were analyzed through thematic analysis guided by Social Cognitive Theory and Social Norms Theory. Findings reveal complex social dynamics influencing food behaviors, including the normalization of specific eating patterns, peer modeling, and the role of observational learning within team environments. This study contributes to the growing body of literature on athlete nutrition and communication, offering insight into how team culture and interpersonal influence affect food decision-making among male distance runners.
Keywords: endurance sports; nutrition; running; journalism; communication; psychology